PROGRAM KEMITRAAN MASYARAKAT (PkM) KELOMPOK USAHA MASYARAKAT PENGOLAH SABUT KELAPA UNTUK COCOPEAT DAN POT TANAMAN - Yuliyanto Yuliyanto; Sugiyarto Sugiyarto; Sukanto Sukanto (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
This PKM activity aims to increase the income of the community, especially housewives in Sungailiat District, Bangka Regency. The program carried out is processing coconut coir into pots and cocopeat. Sungailiat District has a lot of coconut tree plants belonging to the surrounding community, especially in the coastal area. One of the partners for PKM activities is Mr. Karyadi, whose address is in Rebo Village, Sungailiat District, Bangka Regency. Problems that arise in the production process include the length of time required for the process of taking coconut coir and cocopeat powder, which is ± 10 days. Because the process of taking it must be soaked and beaten. The implementation of this activity is carried out by field observation, machine design, machine manufacturing, operation and maintenance training and monitoring and evaluation. The results of this PkM show that the manufacture and procurement of coco decomposing machines for partners has been well realized. There is still a process left because there is an outer part of the coconut husk that is still attached to the machine. This is due to the distance between the wall and the crushing blade having a distance of approximately 15 mm.